(3TQM GdQVi Ydi GdcGajI aj GdfMhs - (3fLe GdOjf QVi GdOjf eMeO Hf GdMSf GdCSJQGHGPi GdfMhis; (3GHf GdMGLH , LeGd GdOjf CHh YeQh GHf GdMGLH, LeGd GdOjf CHh YeQh GHf GdMGLH,J (B646 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LdJ BdGDg Yf Cf JMGW HYO hHYO abO WdH Edi HYV ef CYJfi HUdGM MGdg bhdg GcdeI daX hVY GYfi eaQO s
(3BNQgG (B:s
(3hdG Jdi gPg GdRjGOI gG GdScJ HNdGa RjGOI GdGfcGQ dCf gPg GfeG JRGO EPG de jbUO GdhbJ hGddg CYde HGdUhGH Je GdcJGH s
(3GdfSNI HgG MhGTs
(3HChdgG agQS s
(3HgG fXGe GdJJYbjHIs
(3aQZ GdTGQM ef GdTQM (B683s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdfMhs